2019
DOI: 10.1088/1475-7516/2019/05/053
|View full text |Cite
|
Sign up to set email alerts
|

Testing emergent gravity on galaxy cluster scales

Abstract: Verlinde's theory of Emergent Gravity (EG) describes gravity as an emergent phenomenon rather than a fundamental force. Applying this reasoning in de Sitter space leads to gravity behaving differently on galaxy and galaxy cluster scales; this excess gravity might offer an alternative to dark matter. Here we test these ideas using the data from the Coma cluster and from 58 stacked galaxy clusters. The X-ray surface brightness measurements of the clusters at 0.1 < z < 1.2 along with the weak lensing data are use… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 34 publications
(94 reference statements)
1
12
0
Order By: Relevance
“…Using two relaxed clusters (A2142 and A2319), they found that EG underpredicts the apparent DM mass by a factor of up to a few in the innermost regions of the cluster, but the prediction improved as a function of increasing radius until ∼ r 500 , where the EG prediction and the DM mass estimated from hydrostatic equilibrium matched. Similar trends were noticed by other authors for a number of other systems Halenka et al 2018;Tamosiunas et al 2019).…”
supporting
confidence: 91%
“…Using two relaxed clusters (A2142 and A2319), they found that EG underpredicts the apparent DM mass by a factor of up to a few in the innermost regions of the cluster, but the prediction improved as a function of increasing radius until ∼ r 500 , where the EG prediction and the DM mass estimated from hydrostatic equilibrium matched. Similar trends were noticed by other authors for a number of other systems Halenka et al 2018;Tamosiunas et al 2019).…”
supporting
confidence: 91%
“…5 that LoCuSS (Mulroy et al 2019) results (0.15 < z < 0.3) are in significant tension with Capasso et al (2019). These results, if confirmed, could be used to constrain the models of modified gravity (Arnold, Puchwein & Springel 2014;Sakstein et al 2016;Wilcox et al 2016;Mitchell et al 2018;Tamosiunas et al 2019). Improvements in spectroscopic follow-up of high-z clusters is, however, very critical.…”
Section: R E S U Lt S a N D Discussionmentioning
confidence: 72%
“…Likewise, the ability of measuring cluster masses in different ways (e.g. X-ray astronomy, weak lensing and the Sunyaev-Zeldovich effect) has been explored as a powerful tool for constraining various modified gravity models [11,[24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%